2019
DOI: 10.12688/f1000research.20498.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Clinical Decision Support Systems for the prediction and detection of three disease states in critical care: A systematic literature review

Abstract: Background: Clinical decision support (CDS) systems have emerged as tools providing intelligent decision making to address challenges of critical care. CDS systems can be based on existing guidelines or best practices; and can also utilize machine learning to provide a diagnosis, recommendation, or therapy course. Methods: This research aimed to identify evidence-based study designs and outcome measures to determine the clinical effectiveness of clinical decision support systems in the detection and prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Study protocols identified from bibliographic databases were, however, excluded assuming that final study results would be available and identified elsewhere. The strategy employed in PubMed is provided as Extended data , Table 1–Table 3 2527 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study protocols identified from bibliographic databases were, however, excluded assuming that final study results would be available and identified elsewhere. The strategy employed in PubMed is provided as Extended data , Table 1–Table 3 2527 .…”
Section: Methodsmentioning
confidence: 99%
“…Extended data - Table 2-Search strategy for respiratory distress or respiratory failure in MEDLINE.docx. https://doi.org/10.6084/m9.figshare.9892112.v1 26 .…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The physician can be made aware of their thinking process and can be trained to use or leave out specific values obtained with the clinical examination, or the physician can be trained to reconsider their conclusion when new information is presented. Additionally, machine learning algorithms are increasingly applied in studies to diagnose and predict outcomes of circulatory shock [87]. These types of techniques may be applied to improve the clinical examination as a first step for the evaluation of circulatory shock.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Growing use of electronic health records (EHR) and machine learning have provided a possibility to study large collections of real-world data and develop early detection systems for AKI [10]. Indeed, clinical decision support systems (CDS) have emerged as tools for initial assessment and identification of AKI patients in different settings [11]. These CDS make recommendations and risk stratifications based on the existing guidelines and best practices for AKI [12].…”
Section: Introductionmentioning
confidence: 99%